A Review of the Genus Serratella Edmunds, 1959 in China with Description of a New Species (Ephemeroptera: Ephemerellidae) - Manqing Ding; Luke M. Jacobus; Changfa Zhou (Insects, 2022)
Species in the genus Serratella Edmunds, 1959 from China have never been compared and photographed systematically. Six valid Chinese Serratella species are recognized and revised in this paper. Among them, the imagos of S. brevicauda Jacobus et al., 2009 are unknown; the nymph of this species has a stout, strong body, with remarkably short caudal filaments and maxillary palpi. In contrast, only the imago stage of Serratella fusongensis (Su and You, 1988) (=Serratella longipennis Zhou et al., 1997, syn. nov.) is known; it has relatively long penes with small dorsal projections. The nymphs of S. setigera Bajkova, 1967 have small abdominal tergal spines but distinct, stout, blunt bristles on the spines, and the apexes of the male penes are round and shallowly divided. The fourth species, S. acutiformis sp. nov., which was collected from Western China, has sharp penial apexes (imagos) and large abdominal spines (nymphs). Unlike the former four species, S. ignita (Poda, 1761) and S. zapekinae Bajkova, 1967 has sub-quadrate penes without prominent dorsal projections. The nymph of S. ignita has lateral hair-like setae on the caudal filaments, while the nymph of S. zapekinae lacks such setae but has pairs of tubercles on the head and pronotum. Some characters used in the generic delineation of the genera Ephemerella Walsh, 1862 and Serratella, such as nymphal maxillary palpi and hair-like setae on caudal filaments as well as features of the imaginal penes and forelegs, are varied in Chinese species. However, all species in this paper have bifurcate ventral lamellae of gill VI. Our work highlights a need for further comparative systematic study of the genera Serratella, Ephemerella, and another related genus Torleya Lestage, 1917.